The Effects of Intraarticular and Periarticular Knee Pain Management on the Rehabilitation of Patients with Knee Osteoarthritis after Cephalomedullary Fixation of Pertrochanteric Fractures - Maki Grle; Stefan Moro; Damir Franjić; Dajana Vladić; Robert Karlović; Ivana Grle; Jerko Prlić (Acta Clinica Croatica, 2024)
The gold standard for pertrochanteric fractures is closed reduction with traction and intramedullary osteosynthesis. A significant number of patients report knee pain after surgery, which could be associated with gonarthrosis and traction. In this research we wanted to determine if managing knee pain affects the rehabilitation of patients. There were three groups: the first group received a post-operative intra-articular (IA) injection containing methylprednisolone with lidocaine; the second group received the same combination periarticularly (PA); and the control group did not receive any form of injection. We measured the Visual Analogue Scale (VAS) score on the 3rd and 12th postoperative days, as well as six weeks after surgery. We measured knee range of motion (ROM) on the 12th postoperative day and six weeks after surgery. We calculated the Harris Hip Score (HHS) on the 3rd day and six weeks postoperatively. There were 27 patients. Preoperative Kellgren-Lawrence and VAS pain scores were similar. The IA group demonstrated the lowest VAS pain score after six weeks. ROM did not improve between groups on the 12th day and six weeks postoperatively. HHS was best in the IA group after 6 weeks. Injection of methylprednisolone with lidocaine into the knee improved postoperative rehabilitation in patients with knee osteoarthritis undergoing ipsilateral cephalomedullary fixation for a pertrochanteric fracture.